A TG-FTIR investigation on the co-pyrolysis of the waste HDPE, PP, PS and PET under high heating conditions. Issue 3 (June 2020) - Singh, R.K.; Ruj, B.; Sadhukhan, A.K.; Gupta, P.
Abstract: The present study relates to the investigation of degradation of polymers such as HDPE, PP, PS and PET individually and in mixed forms. Eleven different mixture combinations were analyzed via TG Analysis to determine their degradation behavior individually and in mixed forms. FTIR analysis of the raw polymers was performed to investigate the presence of different functional groups in the sample. Online TG-FTIR analysis was performed to investigate the functional groups present in the volatiles fractions during single component pyrolysis and the interaction of polymers during co-pyrolysis was analyzed, compared and reported. Also, a real-world post consumer mixed waste was also analyzed and compared. During the co-pyrolysis of HDPE with PP and PS, the degradation of PP was delayed whereas PS reduced the degradation temperature of HDPE. In the case of degradation of PS with PP and PET, the increase in degradation temperature was reported whereas, in the case of PET and HDPE mixture, the degradation temperature of HDPE was reduced. During the interaction of PP and PET mixed degradation, PET degradation temperature was delayed. During the FTIR analysis a large amount of alkanes, alkenes, aromatics groups were observed during the degradation of HDPE, PP and PS whereas in case of PET the presence of oxygenated groups is observed. During the mixed degradation, the presence of PET in the sample caused the formation of oxygenated groups by reducing the absorption intensity of other groups or by disappearing the groups. Compounds such as benzoic acid, CO and CO2 was detected during the degradation of PET whereas in other polymers a large amount of methane or methylene group is observed. Overall during the degradation of mixed polymer mixture presence of PET played a vital role in the formation of light gas fractions. Even though a numerous investigation on co-pyrolysis of polymers were available, there is still not sufficient information of interaction of polymers with each other, especially with PET. This article attempts to fill this gap. Highlights: A detailed analysis of the functional group obtained in volatiles via TG-FTIR. HDPE, PP & PS produces high aromatics, alkanes & alkenes functional group. Degradation temperature of PP is delayed in a mixture of HDPE and PP. PS reduces degradation temperature of HDPE and PP in co-pyrolysis. PET degradation temperature is increased in the presence of PP.